2021
DOI: 10.48550/arxiv.2104.08249
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uncovering near-wall blood flow from sparse data with physics-informed neural networks

Amirhossein Arzani,
Jian-Xun Wang,
Roshan M. D'Souza

Abstract: Near-wall blood flow and wall shear stress (WSS) regulate major forms of cardiovascular disease, yet they are challenging to quantify with high fidelity. Patient-specific computational and experimental measurement of WSS suffers from uncertainty, low resolution, and noise issues. Physics-informed neural networks (PINN) provide a flexible deep learning framework to integrate mathematical equations governing blood flow with measurement data. By leveraging knowledge about the governing equations (herein, Navier-S… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…This could help predict local wall shear stress with a better accuracy, which is of interest for drag estimation or for application in bio-medical applications. For instance, Arzani et al [44] use PINNs to estimate near-wall blood flows and wall shear stress which are linked to cardiovascular diseases. The differences of convergence of higher frequency mode shapes can also be explained from a computational point of view: higher frequency modes display smaller structures than low frequency modes.…”
Section: Discussionmentioning
confidence: 99%
“…This could help predict local wall shear stress with a better accuracy, which is of interest for drag estimation or for application in bio-medical applications. For instance, Arzani et al [44] use PINNs to estimate near-wall blood flows and wall shear stress which are linked to cardiovascular diseases. The differences of convergence of higher frequency mode shapes can also be explained from a computational point of view: higher frequency modes display smaller structures than low frequency modes.…”
Section: Discussionmentioning
confidence: 99%
“…In [15], the vanilla PINN was proposed to infer the unknown parameters (e.g., the coefficient of the convection term) in the NS equations based on velocity measurements for the 2D flow over a cylinder. Following this work, PINNs were then applied to various flows [10,11,12,13,14,42,43,44,45,46,47,48,49], covering the applications on compressible flows [13], biomedical flows [14,42,50], turbulent convection flows [48], free boundary and Stefan problems [47], etc. The main attractive advantage of PINNs in solving fluid mechanics problems is that a unified framework (shown in Fig.…”
Section: Recent Advances Of Pinnsmentioning
confidence: 99%
“…PINNs have been used to simulate vortex-induced vibrations (Raissi et al, 2019b) and to tackle ill-posed inverse fluid mechanics problems (Raissi et al, 2020). Moreover, PINNs have been employed for super-resolution and denoising of 4Dflow magnetic resonance imaging (MRI) (Fathi et al, 2020) and prediction of near-wall blood flow from sparse data (Arzani et al, 2021). Recently, Jin et al (2021) showed the applicability of PINNs for the simulation of turbulence directly, where good agreement was obtained between the direct numerical simulation (DNS) results and the PINNs simulation results.…”
Section: Introductionmentioning
confidence: 99%